Ruth Marigu Njue - Karurumo village -- Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Ruth Marigu Njue is a single mother with ten children living in the village Kururumo in Kenya. She is not enjoying farming as she used to and faces a lot of obstacles and problems with the warmer climate and the lack of rains. In the video she talks about the fast-growing crops she cultivates to avoid disease and pests and to adapt to the climate changes she is experiencing. As a way to cope with the droughts she has also begun to plant trees around her farm to attract more rain and water.